Importance of Triguna in Healthy Lifestyle - Girdhar, Shipra; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda the most ancient science of life, practiced in India for thousands of years based on its own unique fundamental principles such as prevention of disease, maintenance of health and promotion of health. Trayopasthamba consists of Ahara (food), Nidra (Sleep) and Brahmacarya (good conducts). Each Upasthamba has its own importance in prevention of disease. Various ancient texts of Yoga, Ayurveda and Puranas talk about the Gunas related to health, behaviour and its effect of the personality in different ways. The concept of Guna dates back to AtharvaVeda, it was discussed in Bhagawad Gita. The concept of Triguna has been utilized to explain the concept of personality in modern era as well. The development of consciousness is apparently rooted in this concept of Triguna. These are known as sattvacalled as stability; Rajas called as activation and Tamas called as inertia. By quantifying those differences in thoughts, one can come to a conclusion where Gunas as a part of personality trait can be studied as aetiology for being diseased or disease free. It helps in building an individual’s personality, depending upon the predominance of Gunas (Sattva, Rajas, and Tamas). Ancient Yogic science classified food in to three basic categories called the Satvik Ahara, Rajasic Ahara and Tamasic Ahara based on their influence on Triguna of mind. In equilibrium, the three Gunas preserve the mind (and indirectly the body), maintaining it in a healthy state or in a state of equilibrium. Any disturbance in this equilibrium results in various types of mental disorders.